2017
DOI: 10.1166/jnn.2017.13743
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bismuth Lipophilic Nanoparticles (BisBAL NPs) on Trichomonas vaginalis Growth

Abstract: The most common treatment to trichomoniasis is the use of metronidazole; however several studies have shown that at least 5% of clinical cases of trichomoniasis are caused by parasites resistant to the drug. Lipophilic bismuth nanoparticles (BisBAL NPs) have an important antimicrobial activity; however the influence of BisBAL NPs on human parasites has not been studied. The objective of this study was to determine the effect of bismuth lipophilic nanoparticles on Trichomonas vaginalis growth. The bismuth nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the present study, as a novel application of this NA, the bactericidal activities of Bi and Ag NPs as well as the Ag–Bi NA were analyzed. In previous works, Ag-rich alloyed NPs, such as those containing Au, Cu, or Pt, demonstrated superior bactericidal properties. Although recent studies have also shown that Bi inhibits some parasitic and microbial growth and that the addition of Bi could modify the final properties of other alloys, , to the best of our knowledge, the bactericidal activity of Ag–Bi NAs has not been studied yet.…”
Section: Results and Discussionmentioning
confidence: 94%
“…In the present study, as a novel application of this NA, the bactericidal activities of Bi and Ag NPs as well as the Ag–Bi NA were analyzed. In previous works, Ag-rich alloyed NPs, such as those containing Au, Cu, or Pt, demonstrated superior bactericidal properties. Although recent studies have also shown that Bi inhibits some parasitic and microbial growth and that the addition of Bi could modify the final properties of other alloys, , to the best of our knowledge, the bactericidal activity of Ag–Bi NAs has not been studied yet.…”
Section: Results and Discussionmentioning
confidence: 94%
“…The antiparasitic effects of bismuth lipophilic nanoparticles (BisBAL NPs) against Trichomonas vaginalis were recently evaluated. The results showed that after 24 h of ex-position to 500 µg mL −1 of BisBAL NPs, the Trichomonas vaginalis growth was inhibited more than 90%, with efficacy similar to metronidazole at 1.3 µg mL −1 , the reference drug [115,116]. This finding is noteworthy because Trichomonas vaginalis is the most common vaginal parasitosis in women worldwide, with about 5% of the trichomoniasis clinical cases being caused by parasites resistant to metronidazole.…”
Section: Antiparasitic Activitymentioning
confidence: 84%
“…The antiparasitic activity of BisBAL NPs on Trichomonas vaginalis was recently studied by Rodríguez-Luis et al [42] Trichomonas vaginalis is the major cause of vaginitis, cervicitis and urethritis in women worldwide. New treatments are expected, because 5% of the trichomoniasis clinical cases are caused by parasites resistant to the reference drug (metronidazole).…”
Section: Bisbal Npsmentioning
confidence: 99%